Hyperuricaemia as a predictor of hospital outcome in patients with sepsis: results of a prospective study - Mir Nadeem (SpringerOpen, 2021)
Abstract Background Early management of sepsis in the emergency department improves patient outcomes. The identification of at-risk patients for aggressive management by an easily available biomarker could go a long way in the triage of patients in the emergency department. It is postulated that during sepsis, the majority of patients undergo ischaemic reperfusion injury or inflammation, and uric acid with its oxidant and antioxidant properties may be playing some role and, hence, the measurement of uric acid could possibly predict the hospital course in patients with sepsis. We were prompted to undertake this study as serum uric acid estimation is readily available and economical compared to newly evolving biomarkers in sepsis. Estimation of serum uric acid levels on arrival to the emergency department may prove a useful predictor of hospital outcome in patients with sepsis especially in regions with limited resources. Results Of 102 patients, 55 (53.9%) were males. The mean age of the study cohort was 63.2 ± 10.48. Patients with higher qSOFA scores had higher uric acid levels on admission. While 12 (11.8%) patients had a septicaemic shock, acute kidney injury was recorded in 48 (47.1%) patients and 11 (10.8%) patients required dialysis. Thirty-four (33.3%) patients had respiratory failure, and of these, 21 (20.6%) patients required mechanical ventilation. The overall median stay in the medical intensive care (MICU) was 3days (range 2–7 days). The patients with higher uric acid levels had higher rates of respiratory failure but did not reach significant levels. In 15 (14.7%) patients, 7 males expired (mortality rate of 14.7%). There was a significant association between SOFA score and mortality. Patients who succumbed to sepsis had higher serum uric acid levels on arrival. Conclusions Patients with higher qSOFA scores had higher uric acid levels on admission. Hyperuricaemia predicted acute kidney injury, a requirement of mechanical ventilation and mean hospital stay in patients with sepsis. Further studies may be required to confirm the association.